Simulation of traffic congestion at the tourist attraction spot of Kuching Waterfront, Sarawak - Jonathan, Sidi; Liew, Wei Fa; Syarul Nizam, Junaini (IEEE, 2009)
This paper presents reports a design and development of an interactive map using Scalable Vector Graphics (SVG). In this paper we used this map to simulate traffic congestion at the tourist attraction spot of Kuching Waterfront, Sarawak. We argue that with our map application, the tourists are able to plan their way by finding and selecting the shortest path along the intended route